2009
DOI: 10.1186/1471-230x-9-85
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, double-blind, placebo-controlled parallel-group dual site trial to evaluate the effects of a Bacillus coagulans-based product on functional intestinal gas symptoms

Abstract: BackgroundThis randomized double blind placebo controlled dual site clinical trial compared a probiotic dietary supplement to placebo regarding effects on gastrointestinal symptoms in adults with post-prandial intestinal gas-related symptoms (abdominal pain, distention, flatulence) but no gastrointestinal (GI) diagnoses to explain the symptoms.MethodsSixty-one adults were enrolled (age 36.5 ± 12.6 years; height 165.1 ± 9.2 cm; weight 75.4 ± 17.3 kg) and randomized to either Digestive Advantage™ Gas Defense For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 10 publications
1
48
0
Order By: Relevance
“…The majority of the 70 studies (Table S1) focused on IBS (based on Rome I, II or III criteria or physician diagnosis; 34 studies), antibiotic‐associated diarrhoea (13 studies) or diarrhoea‐associated Helicobacter pylori eradication therapy (7 studies). Other conditions were investigated in 16 studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the 70 studies (Table S1) focused on IBS (based on Rome I, II or III criteria or physician diagnosis; 34 studies), antibiotic‐associated diarrhoea (13 studies) or diarrhoea‐associated Helicobacter pylori eradication therapy (7 studies). Other conditions were investigated in 16 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies investigated the effect of 6 different probiotics on distension/bloating in indications other than IBS. One of these studies (included in the original consensus) evaluated symptoms related to post‐prandial intestinal gas as a primary endpoint in healthy individuals and reported no significant differences between the probiotic and placebo groups . The remaining 5 studies (examining 5 different probiotics) evaluated distension/bloating as a secondary endpoint.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results of this study showed that probiotic supplementation in stroke patients admitted to the ICU increased frequency of bowel movements and constipation, and could possibly improve complications of constipation in these patients [20]. In research by Kalman et of Bacilus Coagulate on functional intestinal gas symptoms" carried out it was found that consumption of products containing Bacillus Coagulan reduce gastrointestinal symptoms associated gases of meals, especially abdominal pain and distention after a meal linked (p=0.046) [21]. Overall the results of this study showed that consumption of symbiotic supplement in stroke patients admitted to the ICU increased frequency of bowel movements and constipation and could possibly improve discomfort caused by abdominal bloating in these patients.…”
Section: Discussionmentioning
confidence: 64%
“…This strain is characterized by certified beneficial effects in gastrointestinal disorders, such as irritable bowel syndrome, intestinal gas, and colitis (2, 3, 4, 5); in rheumatoid arthritis (6); and in common viral infections of the respiratory tract (7). As a sporeformer, B. coagulans GBI-30, 6086 can be incorporated into foods, where it can survive the mild heat-treatments used for sterilization andwithstand the harsh conditions of the gastrointestinal tract, i.e., the low pH of the gastric barrier (8).…”
Section: Genome Announcementmentioning
confidence: 99%